Development of a model to improve first line leader effectiveness - Burger, Anton (My University, 2015)
There are many leadership development programs available that are aimed at developing first line leaders. These programs are mainly focused on classroom and theoretical training and in most cases lack the translation into operational behaviours and actions that link to the daily operational activities. Every company requires operations management to execute the operations strategy. The operations management function can be defined as the arrangement of resources that are devoted to the production and delivery of products and services. This arrangement of resources requires a person or persons in the organisation who have particular responsibility for managing some or all of the resources which comprise the operations function. This person is the first line leader who performs similar roles to top management, just within their own teams. Thus, the main responsibility of a first line leader is to ensure that the teams (people) produce the required throughput, when they are required to do it and at the right levels of quality, costs and safety. This establishes a causal link between first line leader effectiveness, team effectiveness and overall organisational performance. This forms the theoretical propositions of this research. A case study research method was used to understand the theoretical propositions and analysed the impact of a leadership development program on overall organisational performance in a mass services environment in a short term insurance company in the financial services sector in South Africa. A conceptual framework was developed and tested through an explanatory single case study with eight embedded units (first line leaders) across five business areas consisting of ninety team members. The observations and tests were completed over a 12 month period between January 2013 and February 2014, using explanation building and time-series analysis techniques as an analytic strategy with a multi-method approach (using three measurement systems) to triangulate the data sources to answer the research question. Not only did the organisational performance show an improvement in the majority of the business areas that participated together with a statistically significant improvement in the competencies, but it is also believed that the conceptual framework addressed four common mistakes that are usually made with leadership development programs, i.e., overlooking context, decoupling reflection form real work, underestimating mind-sets, and failing to measure results.